Silver Orthophosphate Immobilized on Flaky Layered Double Hydroxides as the Visible-Light-Driven Photocatalysts. (13th December 2011) - Cui, Xianlu; Li, Yaogang; Zhang, Qinghong; Wang, Hongzhi
Abstract : Flaky layered double hydroxide (FLDH) was prepared by the reconstruction of its oxide in alkali solution. The composites with FLDH/Ag3 PO4 mass ratios at 1.6 : 1 and 3 : 1 were fabricated by the coprecipitation method. The powders were characterized by X-ray diffraction, field-emission scanning electron microscopy, transmission electron microscope, and UV-vis diffuse reflectance spectroscopy. The results indicated that the well-distributed Ag3 PO4 in a fine crystallite size was formed on the surface of FLDH. The photocatalytic activities of the Ag3 PO4 immobilized on FLDH were significantly enhanced for the degradation of acid red G under visible light irradiation compared to bare Ag3 PO4 . The composite with the FLDH/Ag3 PO4 mass ratio of 3 : 1 showed a higher photocatalytic efficiency.